1988
DOI: 10.1200/jco.1988.6.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of epidoxorubicin and doxorubicin in humans.

Abstract: Pharmacokinetics of doxorubicin (DOX), epidoxorubicin (EPI), and their metabolites in plasma have been performed in eight patients receiving 40 to 56 mg/m2 of both anthracyclines as a bolus injection in two sequential cycles. Terminal half-life and volume of distribution appeared to be smaller in case of EPI, whereas plasma clearance and cumulative urinary excretion was larger in comparison to DOX. The major metabolite of DOX was doxorubicinol (Aol) followed by 7-deoxy-doxorubicinol (7d-Aolon). Metabolism to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(87 citation statements)
references
References 23 publications
10
75
0
2
Order By: Relevance
“…This observation seems to be explained by the fact that the antineoplastic effect of CE treatment is mostly attributable to epirubicin, and epirubicin is not metabolized by CYP3A4, 14 whereas cyclophosphamide is partly metabolized by CYP3A4. 15 Thus, the association between response and intratumoral CYP3A4 mRNA expression is considered to be specific to DOC, which is metabolized by CYP3A4.…”
Section: Discussionmentioning
confidence: 92%
“…This observation seems to be explained by the fact that the antineoplastic effect of CE treatment is mostly attributable to epirubicin, and epirubicin is not metabolized by CYP3A4, 14 whereas cyclophosphamide is partly metabolized by CYP3A4. 15 Thus, the association between response and intratumoral CYP3A4 mRNA expression is considered to be specific to DOC, which is metabolized by CYP3A4.…”
Section: Discussionmentioning
confidence: 92%
“…These observations may be attributed to the fact that DXR was difficult to detect at 168 h after dosing at levels of below 24 mg m À2 , possibly resulting in an underestimation or an overestimation of the tails of the clearance curve. The half-lives (t 1/2a , t 1/2b , and t 1/2g ) were longer for NK911 than for free DXR (Mross et al, 1988). The AUC of NK911 was twofold larger than that of free DXR at a dose of 50 mg m À2 .…”
Section: Pharmacokineticsmentioning
confidence: 91%
“…We showed that the prodrug Epi-glu is 100-1,000 times less toxic than Epi and can be completely hydrolysed by the GUS-MAb conjugate bound to tumour cells into the active cytotoxic Epi is an active anti-tumour agent in patients with breast cancer, lymphomas, ovarian cancer, and soft-tissue sarcomas (Cersosimo & Ki Hong, 1986). Epi-glu is a naturally occurring metabolite in patients treated with Epi and the pharmacokinetics are well known (Mross et al, 1988). We used Epi-glu as a model prodrug.…”
Section: Discussionmentioning
confidence: 99%